Recent advances in antimicrobial surfaces for urinary catheters - Rita Teixeira Santos (2022)
Although urinary catheters (UCs) are one of the most used medical devices, they are related to a high incidence of urinary tract infections resulting from microbial colonization and consequent biofilm development on UC surfaces. Currently, a panoply of antimicrobial and antifouling surfaces is available to solve this longstanding problem. However, despite their high performance, these surfaces are still far from clinical application. In this current opinion article, we evaluate and critically discuss the antimicrobial performance and applicability of UC surfaces with different antibiofilm mechanisms. It is our opinion that either killing or anti-adhesive coatings are promising in controlling infection development. However, most of them are more effective in delaying microbial adhesion rather than preventing it.